EFFORTS TO PROTECT THE LEGAL AGAINST CURATORS IN THE PROCESS OF SETTLING BANKRUPTCY ASSETS REVIEWED FROM THE BANKRUPTCY LAW (STUDY ON HKPI- COORDINATION OF THE MEDAN REGION) - Sakti Andreas Sinambela; Isnaini; M. Citra Ramadhan (SOSIOEDUKASI, 2026)
This study aims to analyze the legal arrangements regarding the position, authority, and responsibilities of curators in the process of settling bankruptcy assets based on Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations, as well as examining the role of curatorial organizations in providing legal protection against the risks of civil, criminal, and ethical lawsuits faced by curators. This study uses a normative juridical method with a legislative and conceptual approach. Data were obtained through documentation studies, observations, and interviews, then analyzed descriptive-analytically. The results of the study show that the existing legal arrangements have not comprehensively regulated the limits of curatorial authority and accountability, thus creating legal vulnerabilities in practice. Curatorial organizations play a role in providing preventive protection through education and code of ethics, as well as repressive protection through advocacy and legal assistance. However, limited organizational authority and resources hinder the effectiveness of protection, so it is necessary to strengthen regulations and institutions.